Age-related modifications in CYP-dependent drug metabolism: role of stress - Konstandi, Maria; Johnson, Elizabeth O. (Frontiers in Endocrinology, 2023)
Accumulating clinical evidence indicates extensive inter-individual variations in the effectiveness and adverse effects of standard treatment protocols, which are largely attributed to the multifactorial regulation of the hepatic CYP-dependent drug metabolism that is connected with either transcriptional or post-translational modifications. Age and stress belong to the most important factors in CYP gene regulation. Alterations in neuroendocrine responses to stress, which are associated with modified hypothalamo-pituitary-adrenal axis function, usually accompany ageing. In this light, ageing followed by a decline of the functional integrity of organs, including liver, a failure in preserving homeostasis under stress, increased morbidity and susceptibility to stress, among others, holds a determinant role in the CYP-catalyzed drug metabolism and thus, in the outcome and toxicity of pharmacotherapy. Modifications in the drug metabolizing capacity of the liver with age have been reported and in particular, a decline in the activity of the main CYP isoforms in male senescent rats, indicating decreased metabolism and higher levels of the drug-substrates in their blood. These factors along with the restricted experience in the use of the most medicines in childhood and elderly, could explain at an extent the inter-individual variability in drug efficacy and toxicity outcomes, and underscore the necessity of designing the treatment protocols, accordingly.